Integrasi Pendidikan Bisnis dengan Teaching Factory dan Pengaruhnya Terhadap Kesiapan Bekerja Siswa SMK - Ika Zutiasari; Wening Patmi Rahayu; Jefry Aulia Martha; Siti Zumroh (Universitas Negeri Padang, 2021)
This study aims to see the effect of teaching factory learning on work readiness of vocational students majoring in online business and marketing in Malang. The number of samples in this study amounted to 281 vocational students with the criteria of having implemented teaching factory learning in schools and had implemented industrial work practices. The influence test is done using structural equation modeling (SEM). Descriptive analysis was also carried out in this research to provide an overview of the respondent's answers to each question item given in this study. The results of this study indicate that the better the implementation of teaching factory learning will increase motivation, personal maturity, social maturity, form good work attitudes and student work skills as dimensions of the variable work readiness of vocational students. Based on the dimensions of students 'work readiness, teaching factory learning has the greatest impact in shaping students' personal maturity. Overall the results of this study show a positive value so that it can be concluded that the better the teaching of teaching factory is, the better the students' work readiness will be and vice versa.